(untitled) (Journal of Management & Business, 2025)
Currently, States and their institutions face important modernization challenges due to growing competition, the demand for quality goods and services, and the need to improve productivity and institutional competitiveness. Raising awareness among decision makers about the importance of implementing quality management systems and Artificial Intelligence to improve their processes is essential, because by their nature, these institutions need to adapt to the growing demands for efficiency, transparency and responsiveness and face challenges such as resistance to change, excessive bureaucracy and corruption, which hinder continuous improvement and the satisfaction of citizen needs, as well as the complexity of contemporary problems that require greater interaction between citizens and the State. The main objective of this article is to generate a theoretical framework on Public Administration, Quality Management and Artificial Intelligence applied to this Science, based on the scientific study of these topics, and identifying relevant topics, main authors, notable publications, countries with greater academic production, predominant keywords and methodologies used. A quantitative approach was used, applying scientometric analysis, systematic literature review, phenomenology and hermeneutic analysis, to databases and high-impact scientific articles from the Web of Science (WOS), Scopus and Google Scholar platforms. This research facilitates the understanding of the topic and can serve as input for future research in the search to improve Public Administration. In the results, discussions and conclusions, the need to adopt disruptive and innovative ontological and epistemological approaches is revealed that allow us to better address the challenges and trends of this discipline and lines are proposed aimed at strengthening it in order to satisfy the demands of society.